2014
DOI: 10.4236/health.2014.65054
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about abortion law among young women in Iran

Abstract: Young women are at risk of attempting abortion because of their tendency to delay childbearing. In legal limitation for abortion, low information about abortion laws and consequences of unsafe abortion can result in that women refer to illegal providers. This study investigated knowledge of young women about abortion laws, its complications and their consent with intentional abortion. Near to 50% of participants were not informed about national abortion legislation and its criminal law, and more than 66% of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
0
10
1
1
Order By: Relevance
“…While 15.0% of the females thought about fetal right. In contrary to our study, a study in Iran showed that their females had poor knowledge about laws, majority were not aware of the consequences of unsafe abortion and a very low number perceived that abortion must not be allowed at all (23).…”
Section: Resultscontrasting
confidence: 99%
“…While 15.0% of the females thought about fetal right. In contrary to our study, a study in Iran showed that their females had poor knowledge about laws, majority were not aware of the consequences of unsafe abortion and a very low number perceived that abortion must not be allowed at all (23).…”
Section: Resultscontrasting
confidence: 99%
“…Fig 2 outlines the characteristics of the 24 studies included in this review. The majority were cross-sectional studies (22) [ 7 28 ], and two were prospective studies [ 29 , 30 ]. The manuscripts were published between 1995 to 2015, and reported on data from 13 countries (majority low- and middle-income countries).…”
Section: Resultsmentioning
confidence: 99%
“…The manuscripts were published between 1995 to 2015, and reported on data from 13 countries (majority low- and middle-income countries). Thirteen studies (54%) were published in 2011 to 2015 [ 7 11 , 14 , 15 , 17 , 24 26 , 28 ], followed by 10 studies published between 2000 and 2010 [ 13 , 16 , 18 , 20 23 , 27 , 29 , 30 ]. Only one of the included studies was published before 2000 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; lo que determinaba su conocimiento era que la mayor parte de ellas se realizó abortos o tuvo un familiar/amiga que lo hizo y conocían sus complicaciones y riegos por experiencia 15 . Se realizó una encuesta en Irán para conocer si las jóvenes estudiantes obtenían información sobre el aborto y sus complicaciones en el colegio, lo que se obtuvo fue que ambos temas no eran habitualmente tratados en los centros estudiantiles y el escaso conocimiento que poseían era por algunos profesores que hacían temas de educación sexual 16 . Pero difiere con los estudios realizados a las colegialas de Goma, República Democrática del Congo se observó que tenían un conocimiento razonable de abortos ilegales, las diferentes fuentes de las que obtienen información, fueron la radio (66,2%, 217), amigos o compañeros de trabajo (1,7%, 104), padres (1,5%, 5), y la iglesia (0,5%, 2), siendo su fuente común la radio y amigos.…”
Section: Resultsunclassified